Problematika Penerapan Kurikulum Merdeka Dalam Pembelajaran Pendidikan Agama Islam di SMP Negeri 38 Medan - Damanik, Surya Darma (Jurnal Manajemen Akuntansi (JUMSI), 2024)
A problem is an obstacle or problem that cannot be solved so that achieving the goal is hampered and not optimal. The aim of this research is to identify the problems of implementing the Independent Curriculum in Islamic Religious Education Learning at SMP Negeri 38 Medan. This type of research is case study research with a descriptive qualitative approach, data processing techniques in the form of observation, interviews, documentation. The informants who will be studied are Islamic Education teachers, Principals, Head of Curriculum at SMP Negeri 38 Medan. The results of the research show that there are problems with PAI teachers at SMP Negeri 38 Medan. The lack of teachers in understanding the independent curriculum causes the implementation of the independent curriculum to be less than optimal and has an impact on the learning process, while teachers’ problems in creating teaching modules and analyzing learning outcomes are caused by compiling learning outcomes which must be really careful because they are made in phases. Teachers do not fully understand the learning because the planning is very different from the previous curriculum, namely the 2013 curriculum. The solution to overcome the problems surrounding the independent curriculum is that teachers must participate in socialization, workshops and MGMP forums which aim to overcome the problems they face.